TRPV1 on astrocytes rescues nigral dopamine neurons in Parkinson's disease via CNTF - Nam, Jin H.; Park, Eun S.; Won, So-Yoon; Lee, Yu A.; Kim, Kyoung I.; Jeong, Jae Y.; Baek, Jeong Y.; Cho, Eun J.; Jin, Minyoung; Chung, Young C.; Lee, Byoung D.; Kim, Sung Hyun; et al. (OXFORD UNIV PRESS, 2015)
Currently there is no neuroprotective or neurorestorative therapy for Parkinson's disease. Here we report that transient receptor potential vanilloid 1 (TRPV1) on astrocytes mediates endogenous production of ciliary neurotrophic factor (CNTF), which prevents the active degeneration of dopamine neurons and leads to behavioural recovery through CNTF receptor alpha (CNTFR alpha) on nigral dopamine neurons in both the MPP+-lesioned or adeno-associated virus alpha-synuclein rat models of Parkinson's disease. Western blot and immunohistochemical analysis of human post-mortem substantia nigra from Parkinson's disease suggests that this endogenous neuroprotective system (TRPV1 and CNTF on astrocytes, and CNTFR alpha on dopamine neurons) might have relevance to human Parkinson's disease. Our results suggest that activation of astrocytic TRPV1 activates endogenous neuroprotective machinery in vivo and that it is a novel therapeutic target for the treatment of Parkinson's disease.
Keywords: CILIARY NEUROTROPHIC FACTOR; ALPHA-SYNUCLEIN; REACTIVE ASTROCYTES; GLIAL-CELLS; RAT; EXPRESSION; MODEL; OVEREXPRESSION; RECEPTORS; DEGENERATION